2022
DOI: 10.1177/08948453221113545
|View full text |Cite
|
Sign up to set email alerts
|

Protean Career Orientation and Proactive Career Behaviors During School-to-Work Transition: Mechanism Exploration and Coaching Intervention

Abstract: The school-to-work transition (STWT) period is crucial for students, and a protean career orientation (PCO) is important for a successful transition. The present study aimed to examine the effects of PCO on proactive career behaviors, the underlying mechanisms, and the development of PCO using a coaching approach. Study 1 was conducted based on 250 Chinese undergraduate and postgraduate students during STWT using self-reported questionnaires. Statistical results showed that PCO positively predicted proactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…As previous studies (e.g. Zhang et al, 2022) suggested, both intra-(e.g. training) and extra-organizational (e.g.…”
Section: Practical Implicationssupporting
confidence: 64%
“…As previous studies (e.g. Zhang et al, 2022) suggested, both intra-(e.g. training) and extra-organizational (e.g.…”
Section: Practical Implicationssupporting
confidence: 64%
“…A deficiency in one of these can be problematic (Hall, 2004). Protean career orientation means the tendency to acquire new knowledge and skills and being ready for the changing environment, focusing on the values of freedom and autonomy (Zhang, Wang, Zhang, Xu, & Xu, 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…School to work transition period is critical for newcomers (usually university graduates) to labor market. This period is beginning of one's career and the first career transition (Zhang et al, 2022). Proactive career behaviors contribute to successful school to work transition (De Vos et al, 2009).…”
Section: The Present Studymentioning
confidence: 99%